Strengthening the Independence of the Supreme Court of the Republic of Indonesia in the Era of E-Court-Based Judicial Modernization to Realize Just Legal Reform - H. Muhammadiyah Rafiq; Marhaeni Ria Siombo (Indonesian Journal Publisher, 2026)
This study aims to analyze and formulate a model for strengthening the independence of the Supreme Court of the Republic of Indonesia in the era of E-Court-based judicial modernization as part of legal reform in Indonesia. Using normative juridical methods through legislative and conceptual approaches, this study finds that the digitalization of the judiciary as regulated in Supreme Court Regulation Number 1 of 2019 concerning Electronic Court Case Administration and Trials provides benefits in increasing efficiency and transparency, but also poses challenges to judicial independence due to regulatory limitations, potential technological intervention, and weak data protection and system oversight. Therefore, a comprehensive legal reconstruction is needed through strengthening regulations, institutions, and technology to guarantee the complete independence of judges in realizing a just trial.